Legal Accountability in the Bank Jatim Fake Credit Case: Juridicial Review and Liability in Civil and Criminal Law - Ananta, Bintang Rafli; Makhfud, Amirul (Journal Management & Economics Review (JUMPER), 2025)
The case of alleged fictitious loans at Bank Jatim Jakarta Branch, which reached Rp569.4 billion, highlights serious problems in banking management, especially in the provision of credit facilities. This study aims to identify the modus operandi used in the case and analyze the legal liability that can be imposed on the perpetrators. The research method used is normative juridical with a legal and regulatory approach, as well as case analysis based on data obtained from primary and secondary sources. The results of the study show that the modus operandi in this case involves abuse of authority in the credit-granting process, falsification of documents, and negligence in the application of the principle of banking prudence. From a legal aspect, liability in this case can include criminal sanctions based on the Corruption Crime Law as well as civil and administrative liability to the parties involved for the losses suffered. These findings underscore the urgency of strengthening internal banking supervision and the implementation of strict sanctions to prevent the recurrence of similar cases.